POTENSI HUTAN SAGU RAKYAT DI SERAM BARAT, PROPINSI MALUKU - Boen M Pumama; Subandi At; Hendro Prahasto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
Sago, one of some carbohydrate sources which has a great potential as food stock, grows naturally and distribute through out Indonesian archipelago, Maluku is one of several areas having sago forest.The study on sago forest at West Seram in 1979, showed that the number of mature trees per hectare was 17 trees, consisted of several sago species namely tuni, molat and makanaru. The sago production per tree was 419.9 kg of wet sago or 292,5 kg of dried sago.